Self-Assembly of Well Defined PS-b-PDMS Copolymers in Bulk and in Selective Solvent - Ninago, Mario Daniel (2009)
The synthesis of poly(styrene)-block-poly(dimethylsiloxane) (PS-b-PDMS) copolymers through sequential anionic polymerization, and their self-assembly behavior in bulk (thin films) and in solution (nanoparticles) is herein reported. The results obtained in bulk showed the formation of original island-type nanostructures with periodic separation and uniform height for thin films prepared by spin coating on silicon substrates followed by thermo- or solvent annealing, as evidenced by atomic force microscopy (AFM). In selective solvent (dimethylformamide), micellar core (PDMS) - shell (PS) nanoparticles originated upon direct dissolution, and the corresponding structure was determined in details by combining static and dynamic light scattering (SDLS) measurements.